2022
DOI: 10.4314/tjpr.v20i7.17
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of novel natural inhibitors of avian coccidia (Eimeria tenella) through molecular docking

Abstract: Purpose: To identify some natural molecules (inhibitors) against avian coccidia (Eimeria tenella) through molecular docking in order to find the candidate drugs for poultry industry. Methods: The natural compounds, 6’-de-O-acetylcupacinoside, apigenin, artemisinin, cupacinoside, quercetin and rutin, were screened on the basis of previous research data. These biomolecules were selected as potent inhibitors based on extant literature on calcium-dependent protein kinases (CDPKs) in Eimeria tenella. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These interactions further underpin the binding potential of CPD3 and, as a whole, the importance of natural compounds as potential TcGK inhibitors as an alternative option for the treatment of Chagas disease. In previous works, the therapeutic potential of natural compounds has been studied using in silico approach (13). The current work revealed that CPD 3 is a promising inhibitor of T.cruzi glucokinase based on the several interactions it elicited with the key site residues.…”
Section: Exploring the Interaction Dynamics Of Hk With Cpd3mentioning
confidence: 90%
“…These interactions further underpin the binding potential of CPD3 and, as a whole, the importance of natural compounds as potential TcGK inhibitors as an alternative option for the treatment of Chagas disease. In previous works, the therapeutic potential of natural compounds has been studied using in silico approach (13). The current work revealed that CPD 3 is a promising inhibitor of T.cruzi glucokinase based on the several interactions it elicited with the key site residues.…”
Section: Exploring the Interaction Dynamics Of Hk With Cpd3mentioning
confidence: 90%
“…Calcium-dependent protein kinases (CDPKs) are major effector molecules involved in calcium signaling pathways [ 140 ], thereby affecting above-mentioned physiological processes. Recently, molecular docking was used to screen several plant-based natural compounds for their potential inhibitory effects on Eimeria CDPK [ 141 ]. Que had the best interaction with Eimeria CDPK among the tested compounds (i.e., 6′-de-O-acetylcupacinoside, apigenin, artemisinin, cupacinoside, and rutin), with a binding energy of −7.04 kcal/mol.…”
Section: Eimeria Sppmentioning
confidence: 99%